اثر التدريس المتمركز حول الطالب في معالجة تحديات الاندماج الأكاديمي لدى المستجدين بكلية التربية - دريد, فاطمة الهمالي (Al-Qurtas, 2026)
This case stday examines the impact of student choice and interactive teaching techniques specifically structured debates and discussion on the classroom engagement of 15 freshman university students majoring in English language teaching. Many Libyan students enter university with a background in traditional, lecture-based instruction that limits authentic participation and communication growth. Using a muli-method approach including survey, interviews, reflective journals, instructor notes, the study tracked changes in behavioral, emotional, and cognitive engagement over an eight-week period. Findings reveal significant improvement scross all three engagement dimension. Allowing student to vote on weekly topics increased perceived relevance and interest, with the number of students findings topics relevant jumping from 5 to 13. Structured debates successfully prompted active participation, moving the class from a state of baseline silence to a final debate where %100of students contributed simultaneously, small-group discussion provided a “a safespace” that empowred even the most hesitant learners to speak regularly. The results demonstrate that even modest shifts from a teacher-centered to a facilitative role can foster a “virtuous cycle” of engagement. Furthermore, students began to intergrate these interactive methods into their emerging professional identities as future educators. The study concludes that providing autonomy and structured interaction is anevective strategy for revitalizing EFL learning in Libyan context, though it recommends careful scaffolding to mange the initial anxiety associated with active learning.